FEATURES OF OF HEAVY METALS CONCENTRATION INGRAPES AND ITS PRODUCTS - НЕКОС, А. Н.; МАЛЬЧУК, О. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy)
The problem of safety of plant foodstuffs is considered in the article. Results on the analysis of heavy metals concentration are given for vine, vine juice and home wine, the features of their accumulation and migration in plant foodstuffs are identified.